O trabalho docente na educação a distância: professor ou tutor? - Abreu, Thiago Pedro de (2017)
Distance education is a modality of teaching that offers possibility of access in different places, facilitating the management of time in the studies. Despite the benefits it offers, it is questioned in relation to the difficulties of student learning and the performance of tutors who, often, because they do not have specific training to act in distance education, cannot identify their functions as teachers in the teaching process and Learning in virtual environments. Studies on the practice of tutors show that, although they engage in pedagogical practice as tutors and mediators, they do not recognize themselves as teachers. This work aims to investigate the teaching work and the difficulties of the tutors in courses of higher education in the distance modality. It is based on Litwin, Belloni and Mill, with respect to Distance Education and the work of tutors teachers; Concepts of Marcelo Garcia, Tardif and Lessard were used in the central questions of the teaching work; Besides the studies of Pimenta and Nóvoa that contributed with their research on the formation of teachers. The methodology consisted in the application of an exploratory questionnaire and interviews with tutors who work in Higher Education in distance courses. The research sought to know (i) how the subjects became tutors; (ii) the training of these teachers; (iii) as seen in their performance and; (iv) how they carry out their work in Distance Education; (v) the difficulties faced in student learning. For the analyze of the data, a content analysis technique was used to identify four main categories: Training, Identity, Teaching Work and Precarization. The results obtained after the data analysis indicated that the tutors: a) mostly do not have specific training to act in distance education; B) they are in a scenario of difficulties of the students with the use of the technology and the understanding of the proposed activities. The tutors emphasized the precariousness of work in distance education, since many activities are required beyond teaching, and most of them do not recognize themselves as teachers. These results contribute to intensify the issues that guide distance education and the work of tutors.